Solving a radical equation with a quadratic expression under the radical Solve for \( x \), where \( x \) is a real number. \( x=\sqrt{x^{2}+x+6} \) If there is more than one solution, separate them with commas. If there is no solution, click on "No solution".
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the equation \( x = \sqrt{x^{2} + x + 6} \), we start by squaring both sides: \[ x^2 = x^2 + x + 6 \] Then, we simplify this equation: \[ 0 = x + 6 \] This gives us: \[ x = -6 \] Next, we need to check if this is a valid solution by substituting \( x = -6 \) back into the original equation: \[ -6 = \sqrt{(-6)^{2} + (-6) + 6} \] Calculating the right side: \[ \sqrt{36 - 6 + 6} = \sqrt{36} = 6 \] This means: \[ -6 \neq 6 \] Therefore, \( x = -6 \) is not a valid solution. After checking the calculations, we find that the equation has no real solutions since the only candidate we found does not hold in the original equation. No solution.